Survey of the respiratory health of the workers of a talc producing factory. Issue 7 (July 1995) - Wild, P; Réfrégier, M; Auburtin, G; Carton, B; Moulin, J J
Abstract : OBJECTIVES--To assess the effect of an occupational exposure to talc dust on respiratory health. METHODS--166 talc millers from a French factory underwent spirometry and filled in a standardised respiratory questionnaire during their annual medical visit in 1989. A full sized chest radiograph taken in 1987 for the subjects hired before 1982 was also available, for the others a radiograph taken when hired was used. Radiography was repeated in 1992 for all subjects still active at this date (n = 139). The occupational exposure to talc dust was characterised for each workplace with 1440 personal samples collected since 1986 and by semiquantitative estimates of the historical exposure. RESULTS--The geometric mean (range) of estimated exposure was 1.87 (0.5 to 50) mg/m3 and the estimated cumulative exposure at the date of spirometry was > 150 y mg/m3 for 41 subjects. After adjustment for smoking in a linear model the standardised residual values of both forced vital capacity and forced expiratory volume in one second decreased significantly with increasing exposure. The prevalence of dyspnoea also increased after adjustment for smoking categories and age in a logistic regression. The prevalence of small radiological opacities was significantly related to age and to the exposure after adjustment for age and smoking categories. The incidence of new opacities between the two radiographs (11 new opacities with a profusion higher than 0/1) was significantly related to smoking (10 out of 11 are smokers) but not to the exposure. CONCLUSION--This study shows an effect of high levels of talc dust both on functional variables and on the prevalence of small radiological images, but provides no clear evidence about the possible effect of present levels of exposure.